Donor variability in adipose tissue-derived stem cells: implications for the clinical efficacy of autologous fat grafting - Ozal Beylerli; Ilgiz Gareev; Boxian Zhao; Elmar Musaev (Open Exploration Publishing Inc., 2024)
Autologous fat grafting is a common technique in cosmetic and reconstructive surgery, addressing facial rejuvenation, breast contouring, scar mitigation, and soft tissue corrections. However, clinical outcomes can be inconsistent and unpredictable. While extensive research has explored the mechanisms of harvesting, purifying, and transplanting adipose tissue, there is a notable gap in understanding the impact of donor-related factors on fat grafting success. This review aims to fill this gap by examining how variables like donor age, sex, health status, and anatomical site of fat harvest influence the biological efficacy of adipose-derived stem cells (ASCs). Younger donors often exhibit higher ASC proliferation rates and regenerative potential, while older donors may have reduced cell viability. Hormonal differences between sexes and donor health conditions, such as obesity or diabetes, can also impact ASC functionality and graft outcomes. The anatomical source of the fat further affects its cellular composition and regenerative potential. Understanding these donor-related factors is vital for optimizing fat grafting techniques. The review also explores innovative strategies, such as adipose tissue cryopreservation and acellular fat matrices, to mitigate donor variability. These approaches offer promising avenues for enhancing the predictability and effectiveness of fat grafting. By synthesizing current knowledge and highlighting novel strategies, this review aims to improve clinical outcomes and advance the field of aesthetic and reconstructive surgery.